Evaluation of Palliative Care Technical Skills in an Acute Care Setting: A Simulation-Based, Qualitative Assessment - Daniel Boron-Brenner; Alexzandra Gentsch; Jenna Campolieto; Sepehr Sedigh-Haghighat; John Liantonio (American Journal of Hospice and Palliative Medicine®, 2026)
Objectives Emergency physicians frequently encounter patients with serious illness, yet training in palliative care competencies remains inconsistent during emergency medicine (EM) residency. Simulation-based education may provide a method for integrating palliative care principles into EM training. The objective of this study was to qualitatively examine EM residents' perceptions of the intersection between palliative care and emergency medicine following participation in palliative care-focused simulation scenarios. Methods We conducted a qualitative pilot study using thematic analysis of semi-structured interviews with EM residents who participated in palliative care–focused simulation scenarios at an urban Level I trauma center. Post-simulation interviews explored residents' prior experiences, perceived knowledge gaps, emotional responses, and challenges related to palliative care in the emergency department. Interviews were transcribed and analyzed inductively by a multidisciplinary research team. Results Eleven of 51 eligible residents (21%) participated. Primary thematic domains included perceived knowledge deficits, emotional responses to care delivery, and prior clinical experiences. Residents reported uncertainty regarding core palliative care competencies, including interpretation of advance directives, documentation of do-not-resuscitate/do-not-intubate orders, and clinical decision-making during peri-arrest and resuscitation scenarios. Emotional responses included hesitancy and discomfort during high-stakes decision-making, particularly in the setting of limited information. Conclusions Emergency medicine residents reported frequent exposure to palliative care issues in clinical practice but variable preparation and confidence in navigating these encounters. Palliative-focused simulation elicited perceived knowledge gaps and emotional responses relevant to emergency care delivery. Simulation-based education may offer a structured approach to integrating palliative care competencies into EM training.